Manganese-catalyzed direct C-C coupling of -C-H bonds of amides and esters with alcohols via hydrogen autotransfer - Rana, Jagannath; Gupta, Virendrakumar; Balaraman, Ekambaram (Dalton Transactions, 2019)
Herein we report an efficient manganese-catalyzed C-alkylation of unactivated amides and tert-butyl acetate using alcohols as alkylating agents. This elegant approach exhibits a broad substrate scope providing the C-C coupled products of amides via a hydrogen auto-transfer strategy using aryl, heteroaryl, and aliphatic alcohols.

Iron-catalyzed direct julia-type olefination of alcohols - Landge, Vinod G.; Babu, Reshma; Yadav, Vinita; Subaramanian, Murugan; Gupta, Virendrakumar; Balaraman, Ekambaram (Journal of Organic Chemistry, 2020)
Herein, we report an iron-catalyzed, convenient, and expedient strategy for the synthesis of styrene and naphthalene derivatives with the liberation of dihydrogen. The use of a catalyst derived from an earth-abundant metal provides a sustainable strategy to olefins. This method exhibits wide substrate scope (primary and secondary alcohols) functional group tolerance amino, nitro, halo, alkoxy, thiomethoxy, and S- and N-heterocyclic compounds) that can be scaled up. The unprecedented synthesis of 1-methyl naphthalenes proceeds via tandem methenylation/double dehydrogenation. Mechanistic study shows that the cleavage of the C-H bond of alcohol is the rate-determining step.

Recent advances in liquid organic hydrogen carriers: an alcohol-based hydrogen economy - Yadav, Vinita; Sivakumar, Ganesan; Gupta, Virendrakumar; Balaraman, Ekambaram (ACS Catalysis, 2021)
Energy storage and the use of abundantly available feedstock without contributing to the carbon footprint are two significant global challenges. In this regard, the development of high-performance, low-cost, sustainable, and environmentally friendly energy storage and production systems is crucial to fulfill the growing energy demands of the current society. The use of hydrogen will diversify energy sources as it significantly reduces greenhouse gas emissions and environmental pollution during energy conversion. Although the hydrogen economy is quite beneficial, hydrogen storage is still very challenging, and the existing methods suffer from a lot of problems and drawbacks. The conventional liquefaction and compression hydrogen storage technologies are associated with several challenges, including low storage density, boil-off losses, relatively high costs, and safety and transportation concerns. In recent years, liquid organic hydrogen carrier (LOHC) systems have attained a lot of importance as a substitute for the traditional storage methods. Hydrogen storage and transport using LOHCs are based on two-step cycles, such as (i) loading/storage of hydrogen by catalytic hydrogenation of H2-lean compounds and (ii) unloading/releasing hydrogen by dehydrogenating the resulting H2-rich liquids. Since alcohols are widely accessible from various industrial processes or even from biomass-derived precursors, the catalytic acceptorless dehydrogenation of alcohols is an attractive approach for future hydrogen storage applications. Hence, the catalytic dehydrogenation-hydrogenation of alcohols can be used for the development of alcohol-based LOHC systems which are economical, safe, and easy to handle. Further, they are similar to crude oils under ambient conditions and thus are suitable for use in the current energy infrastructure. This Review covers several essential aspects of these developing efficient and abundantly available LOHC systems for efficient hydrogen storage and transport applications. Additionally, reversible LOHC systems based on the catalytic dehydrogenation-hydrogenation of alcohols and their corresponding carbonyl compounds have been discussed.